The Effect of Using Papaya and Watermelon Juice as a Non-Synthetic Buffer on the Quality of Kacang Goat's (Capra Hircus) Liquid Semen During Cold Storage at 5oC - Muhammad Ade Salim; Nursjafani (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
This study examines the role of non-synthetic buffers from watermelon and papaya juice added to coconut water diluent on the liquid semen quality of Kacang goats during cold storage at 5oC for three months. An experimental method was used in which semen from a 2.5-year-old male was collected twice a week using an artificial vagina. The primary ingredients include young coconut water, Viridis, watermelon, papaya, NaHCO3, and Egg Yolk (KT). Furthermore, the observed variables were individual motility, viability, and abnormality. This study used a Randomized Block Design (RAK)) with 3 treatments and 10 replications, namely P0: Coconut Water + NaHCO3 + 10% KT, P1: Coconut Water + Watermelon Juice + 10% KT, and P2: Coconut Water + Papaya Juice + 10% KT. The data were analyzed using Variety Analysis. The results showed the treatment had a significant effect (P<0.01) on individual motility at all storage times, with the best motility up to 120 storage minutes with 61.00±3.16% at P1. Furthermore, the treatment had a significant effect (P<0.01) on viability at all storage times. The best treatment was P0 (72.24±5.28%), and the lowest was P2 (1.40±0.84%), with a shelf life of 120 minutes. The treatment had no effect (P>0.01) on abnormality at all storage times. It can be concluded that the use of watermelon and papaya juice as non-synthetic buffers in coconut water diluent on Kacang goat semen affects motility and viability but has no effect on abnormality.